2015
DOI: 10.1111/anae.13179
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐regression analysis of prophylactic gabapentin for postoperative pain

Abstract: SummaryWe searched MEDLINE, Embase, CINAHL, AMED and CENTRAL databases until December 2014 and included 133 randomised controlled trials of peri-operative gabapentin vs placebo. Gabapentin reduced mean (95% CI) 24-h morphine-equivalent consumption by 8.44 (7.26-9.62) mg, p < 0.001, whereas more specific reductions in morphine equivalents were predicted (R 2 = 90%, p < 0.001) by the meta-regression equation: 3.73 + (À0.378 9 control morphine consumption (mg)) + (À0.0023 9 gabapentin dose (mg)) + (À1.917 9 anaes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
105
3
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 137 publications
(116 citation statements)
references
References 154 publications
(154 reference statements)
5
105
3
3
Order By: Relevance
“…Future reviews could also investigate whether heterogeneity in other outcomes such as pain scores or length of stay can be explained by baseline risk. Our previous work has indicated that this may indeed be the case 10 and other research has shown this may apply to other outcomes such as depression. 142 Such explanation may have clinical implications, as well as allow use of the methods presented in this paper to improve reporting of effect estimates.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…Future reviews could also investigate whether heterogeneity in other outcomes such as pain scores or length of stay can be explained by baseline risk. Our previous work has indicated that this may indeed be the case 10 and other research has shown this may apply to other outcomes such as depression. 142 Such explanation may have clinical implications, as well as allow use of the methods presented in this paper to improve reporting of effect estimates.…”
Section: Discussionmentioning
confidence: 71%
“…137 In our previous meta-analysis with gabapentin, morphine consumption varied even within procedure-specific subgroups and type of surgery was a small determinant of heterogeneity between studies in relation to morphine consumption and pain scores. 10 Our results suggest that expected postoperative morphine consumption (as a surrogate for pain, participant characteristics and concurrent analgesia) is a large determinant of heterogeneity between studies.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations